Pneumomediastinum: a rare complication in COVID-19 patients - Guerra, Francesco Saverio; Piccarreta, Roberta; Carpentiere, Rossella; Panunzio, Annalori; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
A 62-year-old man with COVID-19 had PS for fever, coughing, and breathlessness. Two days after therapy, the patient’s clinical condition worsened. X-ray and CT showed pneumomediastinum, emphysema and pneumothorax. The patient was intubated and subjected to conservative therapy. The patient was discharged after about 20 days.Radiological imaging plays a key role in the proper diagnosis and treatment of COVID-19 patients with related complications.